Efficient search algorithms for adaptive filtering - Zhao, Cheng. (2008)
The performances of various adaptive filtering algorithms are evaluated based on their convergence rate, computational requirements, misadjustment, and numerical robustness. Improvements to the performance of adaptive filters by using new adaptation algorithms and by the use of recursive structures are reported in the thesis.